(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study sets out to explore the concept of honour killing in Imayam’s novella Pethavan which has been translated into English with the title of The Begetter by Gita Subramanian. It studies various factors in association with honour killing including, caste discrimination, violence and exploitation against women in the name of caste chastity. According to Imayam, intermediate communities do not entertain exchanging their offspring with other communities by their women. Consequently, men perform violence against women if they fall for Dalit men. The novella shatters every disbelieves and influences one to comprehend the viciousness enforced on the Dalit community and women as well. Highlighting individuals who are caught in the viciousness of caste chastity and honour killing, Imayam arouses the conscience of the public to realize the damages caused by social differences and exploitations. On the whole, the study concludes with the idea, it is the misconception of the ancestor’s communal ethics forms the primary reason for the crimes committed by the people in disguise of honour.